Cover Feature: Small Structural Changes in the Alkyl Substituents of Macrocyclic π‐Extended Thiophene Oligomers Causes a Key Effect on Their Stacking and Functional Properties (ChemPlusChem 6/2019). Issue 6 (15th May 2019) - Fujiwara, Toshihiro; Takashika, Masataka; Hasegawa, Masashi; Ie, Yutaka; Aso, Yoshio; Aoyagi, Shinobu; Otani, Hiroyuki; Iyoda, Masahiko
Abstract : The cover feature shows the columnar stacking of a macrocyclic π‐extended thiophene hexamer bearing four butyl groups. The red‐orange and yellow stools represent how this macrocycle adopts different conformations in the solid state and forms crystal polymorphs with varying colors that arise from the induced‐fit stacking of macrocycles. More details can be found in the Full Paper by M. Iyoda, M. Hasegawa, H. Otani, and co‐workers onpage 694 in Issue 6, 2019 (DOI:10.1002/cplu.201900062 ).